Comparative effectiveness of oral antibiotic regimens for urinary tract infections in outpatients: a systematic review - Hoda, Mehnaz; Amin Ahmad, Sabir; Hoda, Afreen (International Journal of Basic & Clinical Pharmacology, 2025)
Urinary tract infections (UTIs) are one of the most prevalent bacterial infections encountered in outpatient clinical practice, especially among women. The treatment of uncomplicated UTIs predominantly involves oral antibiotic therapy; however, the increasing prevalence of antimicrobial resistance presents a significant challenge in selecting the most effective regimen. This systematic review critically evaluates and compares the effectiveness and safety of various oral antibiotic regimens used for the treatment of uncomplicated UTIs in outpatient populations. The study synthesizes evidence from randomized controlled trials (RCTs), cohort studies, and observational studies to identify antibiotics that provide superior symptom resolution, microbiological cure, and lower recurrence rates, while considering patient demographics, local antimicrobial resistance patterns, and adverse effect profiles. The findings suggest that fluoroquinolones, particularly norfloxacin and ofloxacin, demonstrate lower treatment failure rates compared to trimethoprim-sulfamethoxazole (TMP-SMX) and ciprofloxacin. However, the review also emphasizes the need for caution in the use of fluoroquinolones due to their associated side effects and rising resistance. This study aims to guide clinicians in making evidence-based antibiotic choices to optimize patient outcomes and support antimicrobial stewardship efforts in outpatient care.